Web-based Image Steganography Application to Hide Secret Messages - Canistya Chandra, Putu Isthu; Suhartana, I Ketut Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 3 (2021): JELIKU Volume 9 No 3, Februari 2021, 2021)
The Internet has become a very popular medium for communicating and exchanging information data. However, with the development of technology, information data theft is becoming more frequent so it is very necessary to maintain the security of information data. To maintain the security of information data, steganography can be used, namely hiding data or information to a medium. Least Significant Bit (LSB) is a method that can be used to perform the insertion. The Least Significant Bit (LSB) replaces the insignificant or smallest bit value so that when an insertion is done, the difference is not clear. So, this research aims to make a steganography application using the Least Significant Bit (LSB) method.